The Mediation Effect of Employee Engagement on the Relationship Between Employee Relations and Organizational Performance - Asare Duffour, Kwame; Atiim, Edith; Batuuro, Emmanuel (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study examines the mediating role of employee engagement in the relationship between employee relations and organizational performance within a public-sector context in Ghana. Design/methodology/approach: Using a cross-sectional explanatory design, data was collected from 171 employees in the public-sector through a structured questionnaire. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the developed hypotheses. Research Findings: The findings reveal that employee relations significantly influence both employee engagement and organizational performance. Moreover, employee engagement mediates the relationship between employee relations and organizational performance, indicating that creating strong employee relations enhances engagement, which in turn improves organizational performance. Theoretical Contribution/Originality: The study's originality lies in its focus on the public sector in Ghana, providing valuable knowledge that could guide human resource strategies aimed at improving organizational performance through enhanced employee engagement and relations. This research contributes to the literature by exploring the under-investigated role of employee engagement as a mediator in the relationship between employee relations and organizational performance, particularly in the public sector of a developing country.